2004
DOI: 10.2337/diabetes.53.9.2346
|View full text |Cite
|
Sign up to set email alerts
|

Glucokinase Is an Integral Component of the Insulin Granules in Glucose-Responsive Insulin Secretory Cells and Does Not Translocate During Glucose Stimulation

Abstract: The association of glucokinase with insulin secretory granules has been shown by cell microscopy techniques. We used MIN6 insulin-secretory cells and organelle fractionation to determine the effects of glucose on the subcellular distribution of glucokinase. After permeabilization with digitonin, 50% of total glucokinase remained bound intracellularly, while 30% was associated with the 13,000g particulate fraction. After density gradient fractionation of the organelles, immunoreactive glucokinase was distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 39 publications
(37 reference statements)
2
46
0
1
Order By: Relevance
“…It has been argued that acute glucose exposure mediates association of mitochondria with glucokinase (39). While such a process is consistent with the ⌬⌿ fuel response observed here, it has not been corroborated in other studies (40). Recently, a specific plant hexokinase (HXK1), mutated to lack catalytic activity, was shown to still support various signaling functions, thus uncoupling its glucose sensing and subsequent signaling from glucose metabolism (41).…”
Section: Discussionsupporting
confidence: 66%
“…It has been argued that acute glucose exposure mediates association of mitochondria with glucokinase (39). While such a process is consistent with the ⌬⌿ fuel response observed here, it has not been corroborated in other studies (40). Recently, a specific plant hexokinase (HXK1), mutated to lack catalytic activity, was shown to still support various signaling functions, thus uncoupling its glucose sensing and subsequent signaling from glucose metabolism (41).…”
Section: Discussionsupporting
confidence: 66%
“…GK Activity Assay-GK activity was determined from the difference in glucose phosphorylating activity at 0.5 and 100 mM glucose, representing low K m and total hexokinase activity, respectively, using a previously described method (36).…”
Section: Glucose Oxidation and Oxygen Consumption-[u-mentioning
confidence: 99%
“…Rizzo et al (69) showed that high glucose released GK from insulin granules to the cytoplasm in ␤TC3 cells. In MIN6 cells, however, GK association with components of the granule membrane of dense insulin granules and low-density organelles was not affected by glucose (42). In ␤TC3 cells, the interaction between GK and insulin granules proved to be dependent on the generation of nitric oxide (NO), and GK was also associated with neuronal NO synthase, thereby regulating NO synthesis in insulin-secreting cells (70).…”
Section: Glucokinase Regulation In Pancreatic ␤-Cellsmentioning
confidence: 99%
“…By the use of cell imaging techniques and subcellular fractioning of primary ␤-cells and insulin-producing cell lines, it could be demonstrated that GK binds to insulin secretory granules (42,(67)(68)(69)(70). This explains the punctate pattern of GK and a costaining with insulin in ␤-cells (69).…”
Section: Glucokinase Regulation In Pancreatic ␤-Cellsmentioning
confidence: 99%